Analisis Proses Transfer Molding Pembuatan Semiconductor Package Pada New Remocon - Rizky Miftahul Amri; Kardiman Kardiman; Aripin Aripin (Jurnal Ilmiah Wahana Pendidikan, 2022)
The manufacturing process is the processing of a raw material into a product. An example of a material used for manufacturing is plastic. Currently, more than 99% of microelectronic devices are packaged in plastic. One of the manufacturing processes used is transfer molding. Transfer molding is the most commonly used encapsulation method for integrated circuit technology in closed molding using thermosetting plastics which are transferred under pressure. The results of the observations that have been made, transfer molding aims to create a package that protects the chip and wire from the outside environment, electrical connections with the outside, releases heat, and makes assembly easier. The transfer molding process parameters include mold temperature, transfer pressure, mold-clamping pressure, and time to fill the cavity.